Development of progressive competencies for special education practitioners - Bustos, Marie Therese Angeline P. (2008)
The study aimed to establish the competencies for various special education practitioners through the use of the Delph method. Three surveys were conducted. The final progressive SPED competency framework has 81 knowledge and skill competencies under seven strands namely: Foundations Instructional Planning, Instructional Methods and Strategies, Learning Environment, Assessment and Evaluation, Collaboration, and Personal Growth and 16 professional dispositions. The results of the study strengthened the knowledge base of special education teachers through training programs and improved practice.